2019
DOI: 10.1093/infdis/jiz415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seasonal Malaria Chemoprevention on Immune Markers of Exhaustion and Regulation

Abstract: Background Seasonal malaria chemoprevention (SMC) is a novel strategy to reduce malaria infections in children. Infection with Plasmodium falciparum results in immune dysfunction characterized by elevated expression of markers associated with exhaustion, such as PD1 and LAG3, and regulatory CD4+FOXP3+ T cells. Methods In the current study, the impact of seasonal malaria chemoprevention on malaria-induced immune dysfunction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…After the administration of SMC, the authors of a study in Ouessebougou in central Mali measured the level of IgG-type antibodies against specific malaria antigens. These results show the presence of the antibodies [ 10 ]. However, the IgG amount was not proportional to the number of passages received by the child but was higher compared to children who did not receive SMC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the administration of SMC, the authors of a study in Ouessebougou in central Mali measured the level of IgG-type antibodies against specific malaria antigens. These results show the presence of the antibodies [ 10 ]. However, the IgG amount was not proportional to the number of passages received by the child but was higher compared to children who did not receive SMC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy consists of administering a single dose of SP and a dose of Amodiaquine for three days, in four rounds, to children aged 3–59 months and, recently, 5 to 10 years old [ 10 , 11 ]. SMC pilot studies showed encouraging results, with a reduction in the number of malaria and anemia cases in children aged 6–59 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mali was one of the first countries in the Sahel region to implement SMC in 2012, which has now been gradually rolled out to cover the entire country. 8 As of 2020, 13 countries have adopted SMC (Benin, Burkina Faso, Cameroon, Chad, Gambia, Ghana, Guinea, Guinea Bissau, Mali, Niger, Nigeria, Senegal, and Togo) at different scales of implementation. 9 Several studies in Africa have shown that this intervention is cost-effective, safe, and feasible for the prevention of malaria among children in areas with highly seasonal malaria transmission.…”
Section: Introductionmentioning
confidence: 99%